Exploring the Potential of Ultrasound-Guided 5% Dextrose Prolotherapy for Partial Achilles Tendon Tear: A Case Report - Lita DN Tambunan; Widiya Rahmi (The ASEAN Journal of Military and Preventive Medicine, 2025)
Background: Partial Achilles tendon tear may cause persistent heel pain, gait disturbance, and functional limitation when tendon healing is incomplete. Conservative treatment is commonly selected for partial tears, while surgical repair is usually reserved for severe or refractory cases. This case report aims to describe the clinical outcome of ultrasound-guided 5% dextrose prolotherapy as an adjunctive non-surgical treatment for partial Achilles tendon tear. Case illustration: A 35-year-old man presented with sharp pain and tenderness in the left heel after approximately 30 minutes of walking. Ultrasound examination confirmed a partial Achilles tendon tear measuring 0.5 cm, located approximately 2 cm proximal to the calcaneal insertion. Conservative management was initiated within 48 hours after injury, including immobilization in plantarflexion, strict non-weight-bearing, and structured rehabilitation. The patient received three weekly sessions of ultrasound-guided 5% dextrose prolotherapy, with 3 cc injected per session into the margins and center of the tendon tear. Discussion: Pain and tenderness improved within two weeks, with the Visual Analog Scale score decreasing from 5/10 to 1/10. Follow-up ultrasound one month after the final injection showed a more well-defined Achilles tendon and reduction of the tendon gap from 0.32 cm to 0.24 cm. Conclusion: Ultrasound-guided 5% dextrose prolotherapy combined with structured rehabilitation may be a feasible adjunctive non-surgical option for partial Achilles tendon tear, although larger controlled studies are required.